That's a case of sexual harassment ... isn't it? - Kulkarni, Vaibhavi (London : Indian Institute of Management, Ahmedabad, 2019)
The case revolves around a senior official in an Indian private sector bank, who becomes aware of a potential sexual harassment case within his team. The case captures his reactions, right from his initial attempt to understand the scenario, to his conversations with the woman concerned, and his eventual attempt to minimise the incident. The case is based on an actual incident that was recounted by a high level executive who had to deal with such an incident at workplace. The purpose of the case is to explore how such incidents typically play out in the Indian corporate sector, where executives are often desensitised to the comments, jokes and narratives that are sexists in nature, often bordering on sexual harassment or gender-based harassment.
Originally Published InKulkarni, V. (2019). That's a case of sexual harassment... Isn't it? IIMA/COMM0021. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sexual harassment -- Case studies; Professional ethics -- Case studies; Personnel management -- Case studies